Profitability, Liquidity, Board Size, and Gender Diversity on Financial Distress - Khoir, Rif'ah Khusniah Aimmatul; Wafiroh, Novi Lailiyul (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
The company was founded with the hope of making a profit, but when the profits obtained experience a continuous decline, it can result in financial distress, where the company's financial condition experiences a decline in income. Financial distress can occur due to two indicators: financial and non-financial. This research aims to analyze the influence of profitability, liquidity, board size, and gender diversity on financial distress. The companies used as research samples are transportation and logistics companies in 2018–2022, with a total of 80 company samples during the research period. Using a quantitative approach with purposive sampling methods. In hypothesis testing, the analysis chosen is panel data analysis using the Eviews12 program. The research shows that profitability and liquidity have an effect on financial distress. It can be concluded that when the company has profitability and liquidity that tend to be low, the level of financial distress will tend to be high. While board size and gender diversity have no effect on financial distress, through these findings, it is known that board size and gender diversity are not able to guarantee that the company can avoid financial distress problems.